Are the tests scores of the Programme for International Student Assessment (PISA) and the National Educational Panel Study (NEPS) science tests comparable? An assessment of test equivalence in German Schools. (December 2018) - Wagner, Helene; Hahn, Inga; Schöps, Katrin; Ihme, Jan Marten; Köller, Olaf
Highlights: The science tests from PISA and NEPS are similar with regard to their constructs. The linking of the test scores showed a high classification consistency. The classification consistency was highest when missings were ignored in both tests. Abstract: The aim of this study is to link the science scale of the German National Educational Panel Study (NEPS) with the science scale of the Programme for International Student Assessment (PISA). One requirement for a strong linking of test scores from different studies is a sufficient similarity of the tests regarding their constructs. The present study aims to assess the similarity of the operationalized constructs of the NEPS and PISA scientific literacy tests with the aim to link the scales of the two tests. A linking study was carried out for this purpose in which 1079 students worked on the tasks of both studies. The results of the comparison between NEPS and PISA indicated a high overlap regarding their constructs. However, both studies deal with missing responses differently. The linking via equipercentile equating showed a high classification consistency which was highest when missing responses were ignored in both studies.